The impact of oil price fluctuations on the growth of the economies of oil-exporting countries - Belkacem, Manel (Milev Journal of Research and Studies, 2017)
Oil price fluctuations are important factor affecting the global Economic growth. This study has concluded that these fluctuations affect in two different ways oil-exporting countries: first one is considered positive by increasing financial returns, hence resulting on an increasing economic growth across all sectors; while the second is considered negative due to lower financial returns and accompanying decline in economic growth rates.